Responses of arbuscular mycorrhizal fungi to long-term inorganic and organic nutrient addition in a lowland tropical forest - Sheldrake, Merlin (ISME J, 2018)
Improved understanding of the nutritional ecology of arbuscular mycorrhizal (AM) fungi is important in understanding how tropical forests maintain high productivity on low-fertility soils. Relatively little is known about how AM fungi will respond to changes in nutrient inputs in tropical forests, which hampers our ability to assess how forest productivity will be influenced by anthropogenic change. Here we assessed the influence of long-term inorganic and organic nutrient additions and nutrient depletion on AM fungi, using two adjacent experiments in a lowland tropical forest in Panama. We characterised AM fungal communities in soil and roots using 454-pyrosequencing, and quantified AM fungal abundance using microscopy and a lipid biomarker. Phosphorus and nitrogen addition reduced the abundance of AM fungi to a similar extent, but affected community composition in different ways. Nutrient depletion (removal of leaf litter) had a pronounced effect on AM fungal community composition, affecting nearly as many OTUs as phosphorus addition. The addition of nutrients in organic form (leaf litter) had little effect on any AM fungal parameter. Soil AM fungal communities responded more strongly to changes in nutrient availability than communities in roots. This suggests that the ‘dual niches’ of AM fungi in soil versus roots are structured to different degrees by abiotic environmental filters, and biotic filters imposed by the plant host. Our findings indicate that AM fungal communities are fine-tuned to nutrient regimes, and support future studies aiming to link AM fungal community dynamics with ecosystem function.